The willingness to tolerate higher levels of peripheral fatigue might explain the improved performance during head-to-head cycling competitions - Konings, M. J.; Parkinson, J.; Micklewright, D.; Zijdewind, I.; Heitinga, F. J. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Perceptual affordances provided by the environment could influence the maximal effort an athlete is willing to exert, and alter pacing behavior and performance (Smits et al. 2014). In this perspective, the presence of an opponent has been shown to improve cycling performance as result of a faster initial pace (Corbett et al. 2012). The present study aimed to explore the potential differences in the origin of fatigue that could explain the performance improvement when racing against opponents. Methods: Twelve moderately trained participants completed a maximal incremental test and three 4-km time trials (TT) on a VeloTron cycle ergometer. After a familiarization TT (TTfam), participants performed in random order a TT with no opponent (TTno) or a virtual opponent (TToppo). Repeated-measures ANOVAs (p<0.05) were used to examine differences in pacing and performance related to power output, velocity, and finishing times. Measures of neuromuscular function for the assessment of central and peripheral fatigue were evaluated before and after the trial by delivering twin electrical stimuli (200-ìs duration; 10ms interval) to the right femoral nerve during MVC and at rest. In total three variables were obtained to quantify muscle performance; the maximal voluntary contraction (MVC), the voluntary activation (VA) and the potentiated twitch (PT). Results: TToppo was completed faster compared to TTno (382.2±31.9s vs. 393.6±21.9s, P=0.022), mainly due to a faster initial pace during TToppo. The reduction in MVC was higher in TToppo compared to TTno (MVCpre-vs-post: -17.5±12.4% vs. -11.4±10.9%, P=0.032). This difference can be assigned to the higher levels of peripheral fatigue found after TToppo compared to TTno (PTpre-vs-post: -23.1±14.0% vs. -16.2±11.4%, P=0.041), while no differences were found for central fatigue (VApre-vs-post: -4.9±6.7% vs. -3.4±5.0%, P=0.274). Discussion: The presence of a competitive opponent seems to enable the participants to use a greater degree of their physiologic capacity that is not fully accessed when competing alone. The present study has shown that the improved performance during head-to-head competitions compared to individual cycling time-trials could be assigned to the willingness to tolerate higher levels of peripheral fatigue.